2020
DOI: 10.1002/hep.31115
|View full text |Cite
|
Sign up to set email alerts
|

Indole Alleviates Diet‐Induced Hepatic Steatosis and Inflammation in a Manner Involving Myeloid Cell 6‐Phosphofructo‐2‐Kinase/Fructose‐2,6‐Biphosphatase 3

Abstract: BaCKgRoUND aND aIMS: Indole is a microbiota metabolite that exerts anti-inflammatory responses. However, the relevance of indole to human non-alcoholic fatty liver disease (NAFLD) is not clear. It also remains largely unknown whether and how indole acts to protect against NAFLD. The present study sought to examine the association between the circulating levels of indole and liver fat content in human subjects and explore the mechanisms underlying indole actions in mice with diet-induced NAFLD. appRoaCH aND ReS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 37 publications
5
102
0
6
Order By: Relevance
“…In addition, supplementation with indole reduced the severity of colitis that was induced by DDS. In another study, it was shown that circulating indole concentrations were inversely correlated with obesity and liver fat content [ 48 ]. Indole reduced the severity of NAFLD caused by an HFD in mice.…”
Section: Gut Microbiota Metabolites In the Pathogenesis Of Nafldmentioning
confidence: 99%
“…In addition, supplementation with indole reduced the severity of colitis that was induced by DDS. In another study, it was shown that circulating indole concentrations were inversely correlated with obesity and liver fat content [ 48 ]. Indole reduced the severity of NAFLD caused by an HFD in mice.…”
Section: Gut Microbiota Metabolites In the Pathogenesis Of Nafldmentioning
confidence: 99%
“…For instance, IAld induced STAT3 (signal transducer and activator of transcription 3) phosphorylation by stimulating the secretion of interleukin-22 (IL-22) via aryl hydrocarbon receptor (AhR) to promote the proliferation of the intestinal epithelial cells, which in turn restores the barrier function [116]. Treatment with indole attenuated high-fat diet-induced severity of hepatic steatosis and inflammation in mice, which was connected with the regulation of PFKFB3 (6-Phosphofructo-2-Kinase/Fructose-2,6-Biphosphatase 3) and the normalization of gut microbiome [117]. Study on rats revealed that IPA facilitated the protection against steatohepatitis induced by high-fat diet, as demonstrated by the improvement of gut dysbiosis and intestinal epithelial barrier function and the inhibition of pro-inflammatory signaling [118].…”
Section: Functional Amino Acids (L-tryptophan and L-glutamine)mentioning
confidence: 99%
“…The latest evidence suggests that indole is relevant to human nonalcoholic fatty liver disease, and can significantly reduce the severity of liver steatosis and inflammation. 26 …”
Section: Introductionmentioning
confidence: 99%